1996
DOI: 10.1063/1.868970
|View full text |Cite
|
Sign up to set email alerts
|

Scalar imaging velocimetry measurements of the velocity gradient tensor field in turbulent flows. II. Experimental results

Abstract: Scalar imaging velocimetry is here applied to experimental turbulent flow scalar field data to yield the first fully resolved, non-intrusive laboratory measurements of the spatio-temporal structure and dynamics of the full nine-component velocity gradient tensor field ٌu(x,t), as well as the pressure gradient field ٌp(x,t), in a turbulent flow. Results are from turbulent flows at outer scale Reynolds numbers in the range 3,000рRe ␦ р4,200, with Taylor scale Reynolds numbers Re Ϸ45. These give a previously inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
37
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 16 publications
11
37
1
1
Order By: Relevance
“…The agreement between the results in Fig. 8 is satisfactory, where PDFs of the production terms show clearly positively skewed distributions, as shown also in Lu¨thi et al (2005) and Su and Dahm (1996b).…”
Section: Resultssupporting
confidence: 69%
“…The agreement between the results in Fig. 8 is satisfactory, where PDFs of the production terms show clearly positively skewed distributions, as shown also in Lu¨thi et al (2005) and Su and Dahm (1996b).…”
Section: Resultssupporting
confidence: 69%
“…This was observed in numerical simulations in different flows (Ruetsch & Maxey 1991, 1992Tsinober 2001;Tsinober & Galanti 2001;Vedula et al 2001;Brethouwer et al 2003 and references therein) at rather small Taylor microscale Reynolds numbers Re λ ∼ 100. No similar results have been obtained so far in the laboratory (with the exception of Su & Dahm (1996), who were able to obtain the alignments between the vector, G, and the eigenframe, λ k , of the rate-of-strain tensor, s ij , in the far field of a turbulent jet flow at Re λ ∼ 50), especially for high-Reynolds-number flows. Instead, a surrogate quantity, the mixed skewness,…”
Section: Introductionmentioning
confidence: 78%
“…The final result in (20) is an operator that extracts the nonlocal background strain rate tensor S B ij at any point x from the total strain rate tensor S ij . For the Taylor expansion in (10), this operator involves Laplacians of the total strain rate field S ij (x).…”
Section: A Evaluating the Background Strain Rate Tensormentioning
confidence: 99%
“…An understanding of how vortical structures are stretched by the strain rate field S ij (x) is thus essential to any description of the energetics of such flows. Over the last two decades, direct numerical simulations (DNS) [5,6,7] and experimental studies [8,9,10,11,12] of the fine-scale structure of turbulence have revealed a preferred alignment of the vorticity with the intermediate eigenvector of the strain rate tensor. This result has been widely regarded as surprising.…”
Section: Introductionmentioning
confidence: 99%